Numerical Study on Optimization of Structural Parameters of Guiding Vane of Longitudinal Ventilation for Highway Tunnel - Shixian Wu; Heqing Liu; Yongping Chen; Haiqiao Wang (Advances in Civil Engineering)
In order to reduce the energy loss during longitudinal ventilation for highway tunnels, a guiding vane was proposed to be installed on the tunnel dome in the downstream of the air supply outlet. The effects of the guiding vane’s angles and equivalent heights on the effectiveness of tunnel ventilation were investigated by the numerical simulation using the CFD approach. When the installation angle of the guiding vane was 2∼5 degrees and the equivalent height was 0.20∼0.35, the guiding vane played a significant role in drag reduction. Under the circumstances, the pressure-rise of air supply outlet was the maximum. The required distance for pressure-rise was approximately 90∼115 m that was not affected by the average air velocity in the tunnel and the structure parameters of the guiding vane.